Quantum cutting adhesive film, solar cell and preparation method thereof

By synthesizing quantum tailored quantum dots in the encapsulated film of solar cells in the in situ, the problems of process pollution and insufficient peeling force in the prior art are solved, and efficient photoconversion efficiency and environmentally friendly production process are achieved.

CN119709050APending Publication Date: 2025-03-28WUXI UTMOST LIGHT TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311269097.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art process of introducing downconverting materials into solar cells can contaminate the environment and reduce the peeling force of the components and the gain effect on light conversion efficiency.

Method used

Quantum tailored quantum dots are synthesized in the encapsulated film by in-situ synthesis. By mixing the raw materials of the quantum tailored quantum dots with plastic materials to form masterbatches, and then forming them in the film, the use of solvents and the separate synthesis process of quantum dots are avoided.

Benefits of technology

This method simplifies the process, avoids environmental pollution, improves the stability of quantum tailored quantum dots and the adhesion of the adhesive film, enhances the photoconversion efficiency of the solar cell, and maintains the peeling force of the module.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709050A_ABST
    Figure CN119709050A_ABST
Patent Text Reader

Abstract

The invention discloses a quantum cutting adhesive film, a solar cell and a preparation method of the quantum cutting adhesive film, belongs to the technical field of solar cells, and overcomes the defects that in the prior art, a process of introducing a down-conversion material into the solar cell can pollute the environment, can reduce the stripping force of an assembly and is poor in light conversion efficiency gain effect. The preparation method of the quantum cutting adhesive film comprises the following steps: step 1, mixing and granulating raw materials required for synthesizing quantum cutting quantum dots with a plastic material respectively to obtain master batches containing corresponding raw materials; and 2, mixing the master batches of the quantum cutting quantum dots, and molding to obtain the quantum cutting adhesive film. The quantum cutting quantum dots are directly synthesized in the adhesive film, so that introduction of a quantum cutting quantum dot coating in the process of preparing the solar cell is avoided, and reduction of the stripping force of the module is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells, and in particular relates to a quantum tailoring adhesive film, a solar cell and a preparation method thereof. Background Art

[0002] Currently in the market, crystalline silicon solar cell modules still account for at least 85% of the market share. However, traditional solar cells such as monocrystalline silicon cells, cadmium telluride cells, and copper indium gallium selenide cells have very weak absorption intensity for ultraviolet light and cannot effectively convert ultraviolet light into electrical energy for utilization, making it difficult to further improve the efficiency of crystalline silicon modules.

[0003] The energy loss of these ultraviolet lights can be utilized by photoluminescent fluorescent materials. The perovskite quantum dots are doped with rare earth elements Yb 3+ 、Ce 3+ , achieving down-conversion quantum tailoring (i.e. emitting multiple near-infrared photons for every UV / visible light photon absorbed), with a quantum efficiency of up to 146%, which can increase the PCE of commercial crystalline silicon solar cells from 18.1% to more than 21.5%. For example, the prior art provides a method for preparing a quantum tailoring coating, which is to dissolve the prepared quantum dot down-conversion material in an organic solvent, and then deposit a layer of toluene solution containing the quantum dot down-conversion material on the surface of one side of the upper encapsulation glass by spin coating, scraping, 3D printing, etc., which becomes a quantum tailoring coating after drying, and finally add a POE or other encapsulation film for lamination to obtain a photovoltaic module.

[0004] However, the above preparation method will produce uneven coffee rings due to the volatilization of the solvent, and the volatilization of the solvent will seriously pollute the environment; on the other hand, due to the absence of a binder, the adhesion of the quantum dot material on the surface of the encapsulation glass is poor after the solvent evaporates, and the coating is very likely to fall off during the component assembly process during industrial production. In addition, during the lamination process, the quantum dot material will continue to diffuse and flow toward the encapsulation film, reducing the uniformity of the coating and sharply reducing the gain effect on the light conversion efficiency. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defects in the prior art of introducing down-conversion materials into solar cells, which will cause pollution to the environment, reduce the peeling force of the components (i.e., the peeling force between the encapsulating glass and the encapsulating film), and have a poor effect on the gain of light conversion efficiency, thereby providing a quantum tailoring film, a solar cell and a method for preparing the same.

[0006] To this end, the present invention provides the following technical solutions.

[0007] In a first aspect, the present invention provides a method for preparing a quantum tailoring adhesive film, comprising the following steps:

[0008] Step 1, mixing the raw materials required for synthesizing quantum tailored quantum dots with plastic materials to obtain masterbatches containing the corresponding raw materials;

[0009] Step 2: Mix the masterbatches of quantum tailored quantum dots to form a quantum tailored film.

[0010] Further, the quantum tailoring quantum dots are rare earth doped perovskite quantum dots, and the perovskite quantum dots are composed of: ABX3;

[0011] Among them, X includes Cl - Br - ,I - At least one of;

[0012] A includes Cs + 、CH3NH3 + 、CH(NH2)2 + At least one of;

[0013] B includes Pb 2+ Sn 2+ , Mn 2+ At least one of;

[0014] The rare earth includes at least one of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), yttrium (Y) or scandium (Se).

[0015] Furthermore, the step 1 comprises:

[0016] The raw material containing A is mixed with the plastic material and granulated to obtain a master batch A; preferably, the mass content of the raw material containing A in the master batch A is 0.5-2%;

[0017] The raw material containing B is mixed with the plastic material and granulated to obtain a master batch B; preferably, the mass content of the raw material containing B in the master batch B is 0.5-2%;

[0018] The raw material containing X is mixed with the plastic material and granulated to obtain a masterbatch X; preferably, the mass content of the raw material containing X in the masterbatch X is 1 to 3%;

[0019] The raw material containing rare earth elements is mixed with the plastic material and granulated to obtain the master batch Re; preferably, the mass content of the raw material containing rare earth elements in the master batch Re is 0.5-2%.

[0020] Furthermore, at least one of the following conditions is met:

[0021] (1) The raw material A includes at least one of cesium stearate, cesium carbonate and cesium acetate;

[0022] (2) the B-containing raw material includes at least one of lead stearate, lead acetate and lead carbonate;

[0023] (3) the X-containing raw material includes at least one of octylamine bromide, oleylamine bromide, dimethyldioctadecyl bromide, octylamine chloride, oleylamine chloride, and dimethyldioctadecyl chloride;

[0024] (4) The raw material containing rare earth elements includes at least one of ytterbium acetate, ytterbium acetate, ytterbium chloride, and ytterbium oxide.

[0025] Furthermore, step 2 also includes the step of adding blank masterbatch, wherein the blank masterbatch is prepared by granulating plastic material; adding blank masterbatch can make the mixing of each component material more uniform, and can also adjust the concentration of quantum tailoring quantum dots in the quantum tailoring film.

[0026] Preferably, when the masterbatches are mixed, the mass ratio of masterbatch A: masterbatch B: masterbatch X: masterbatch Re: blank masterbatch is (20.8-31.2): (39.2-58.8): (100.8-151.2): (19.6-98): (180-102).

[0027] Furthermore, in step 2, after the masterbatches of quantum tailored quantum dots are mixed, the steps of adding a crosslinking agent, a co-crosslinking agent, a coupling agent, a light stabilizer, an antioxidant and an anti-PID aid are also included.

[0028] Furthermore, the plastic material is ethylene-octene copolymer, polyethylene-polyvinyl acetate copolymer or polyvinyl butyral.

[0029] Further, the cross-linking agent is selected from one or more of tert-butyl peroxy-2-ethylhexyl carbonate, tert-butyl peroxy-isopropyl carbonate, dibenzoyl peroxide, diisopropyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, cyclohexanone peroxide, tert-butyl hydroperoxide, tert-butyl perbenzoate, tert-butyl peracetate, di-(4-tert-butylcyclohexyl) peroxydicarbonate, tert-butyl peroxy-3,5,5-trimethylhexanoate, and triallyl isocyanate.

[0030] Furthermore, the auxiliary crosslinking agent is selected from one or more of trimethylolpropane triacrylate, 2-trimethylolpropane tetraacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethyl 4-(dimethylamino)benzoate, and diisopropylbenzene peroxide (DCP).

[0031] Furthermore, the coupling agent is selected from one or more of 3-(methacryloyloxy)propyltrimethoxysilane, 3-glycidylpropyltrimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane and vinyltrimethoxysilane.

[0032] Furthermore, the light stabilizer is selected from one or more of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) succinate, and poly-{[6-[(1,1,3,3-tetramethylbutyl)-imino]-1,3,5-triazine-2,4-diyl][2-(2,2,6,6-tetramethylpiperidinyl)-amino]-hexylene-[4-(2,2,6,6-tetramethylpiperidinyl)-imino]}.

[0033] Furthermore, the antioxidant is one or more of a phenolic antioxidant, a phosphite antioxidant and a hindered amine antioxidant.

[0034] Furthermore, the anti-PID additive is one or more of ethoxylated pentaerythritol triacrylate, aluminum phosphate, titanium phosphate, tin phosphate, zirconium phosphate or bismuth phosphate; the anti-PID additive acts as a metal ion capture agent.

[0035] Furthermore, the amount of the cross-linking agent added is 0.1-1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch.

[0036] Furthermore, the amount of the co-crosslinking agent added is 0.1-1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch.

[0037] Furthermore, the added amount of the coupling agent is 0.1-1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch.

[0038] Furthermore, the amount of the light stabilizer added is 0.1 to 1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch.

[0039] Furthermore, the antioxidant is added in an amount of 0.1 to 1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch.

[0040] Furthermore, the amount of the anti-PID additive added is 0.1-1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch.

[0041] In a second aspect, the present invention provides a quantum tailoring adhesive film prepared according to the above method.

[0042] Furthermore, the thickness of the quantum tailoring film is 0.2 to 0.8 mm.

[0043] In a third aspect, the present invention provides a solar cell, which comprises, in sequence, an upper encapsulation glass, an upper encapsulation film, a battery unit, a lower encapsulation film and a lower encapsulation glass;

[0044] The upper packaging film and / or the lower packaging film is the above-mentioned quantum cutting film;

[0045] Optionally, the battery unit is any one of a crystalline silicon battery, a perovskite battery, a perovskite-crystalline silicon stacked battery, a dye-sensitized battery, a quantum dot photovoltaic, an organic photovoltaic, a copper indium gallium selenide solar device, and a cadmium telluride thin-film solar device.

[0046] In a fourth aspect, the present invention provides a method for preparing a solar cell, characterized in that it comprises taking a battery unit, placing an upper packaging film and a lower packaging film on the upper and lower surfaces thereof respectively, placing an upper packaging glass on the upper packaging film, placing a lower packaging glass under the lower packaging film, and laminating to obtain the solar cell;

[0047] Optionally, the lamination pressure during the lamination process is 20 to 90 kPa, the lamination temperature is 80 to 180° C., and the lamination time is 15 to 30 min.

[0048] The plastic material is any one of ethylene-octene copolymer (POE), polyethylene-polyvinyl acetate copolymer (EVA), and polyvinyl butyral (PVB).

[0049] The technical solution of the present invention has the following advantages:

[0050] 1. A method for preparing a quantum tailoring film, comprising the following steps: step 1, mixing the raw materials required for synthesizing quantum tailoring quantum dots with plastic materials respectively to granulate to obtain masterbatches containing the corresponding raw materials; step 2, mixing the masterbatches of quantum tailoring quantum dots and molding to obtain a quantum tailoring film.

[0051] The invention adopts an in-situ synthesis method to synthesize quantum tailored quantum dots in the process of preparing the encapsulation film, which has a simple process and ensures the stability of the quantum tailored quantum dots. The raw materials are mixed after granulation, so that the raw materials are mixed more fully and evenly, and the doping ratio of the rare earth elements is easier to control.

[0052] The present invention can be compatible with existing photovoltaic module production lines without the need to modify equipment.

[0053] The present invention eliminates the complicated production and purification process of the quantum dot synthesis process alone, does not add solvents, avoids environmental pollution caused by solvent volatilization, and avoids the uneven distribution of quantum tailored quantum dots caused by solvent volatilization. Quantum tailored quantum dots are synthesized in situ, and no high-temperature processes such as granulation and injection molding are required after synthesis. Various high-temperature resistant organic ligands in the adhesive film will not be lost. The ligands can play a good protective role during the high-temperature process, the heat resistance is improved, and the efficiency of the encapsulation process does not decrease, thereby ensuring the quantum efficiency. The quantum tailored quantum dots are directly synthesized in the adhesive film, avoiding the introduction of quantum tailored quantum dot coatings in the process of preparing solar cells, thereby avoiding reducing the peeling force of the components.

[0054] 2. The amount of cross-linking agent added is 0.1-1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch; the amount of the auxiliary cross-linking agent added is 0.1-1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch; the amount of coupling agent added is 0.1-1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch; the amount of light stabilizer added is 0.1-1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch; the amount of antioxidant added is 0.1-1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch; the amount of anti-PID auxiliary agent added is 0.1-1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch.

[0055] The cross-linking agent and the initiator work together to initiate the cross-linking of the polymer, the coupling agent can increase the adhesion between the film and the glass, the light stabilizer increases the light stability of the film, the antioxidant increases the anti-oxidation property of the film, and the anti-PID (PID effect can refer to the potential induced decay effect of the photovoltaic module) auxiliary agent can prevent the potential induced decay effect of the photovoltaic module. By controlling the content of the above components, the film prepared by the present invention has excellent water and oxygen barrier properties, glass adhesion and light resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0057] Figure 1 Schematic diagram of the solar cell structure.

[0058] Reference numerals:

[0059] 1-upper packaging glass, 2-upper packaging film, 3-battery unit, 4-lower packaging film, 5-lower packaging glass. DETAILED DESCRIPTION

[0060] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0061] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0062] Example 1

[0063] This embodiment provides a method for preparing a quantum tailoring adhesive film, comprising:

[0064] (1) 5 g of cesium stearate and 500 g of POE were uniformly mixed and placed in a granulator with a maximum melting temperature set at 180° C. to prepare cesium masterbatch.

[0065] (2) 10 g of lead stearate and 1000 g of POE were uniformly mixed, placed in a granulator and set at a maximum melting temperature of 180° C. to prepare lead masterbatch.

[0066] (3) 20 g of octylamine bromine and 20 g of octylamine chlorine were uniformly mixed with 2000 g of POE, and the mixture was placed in a pelletizer and set to a maximum melting temperature of 180° C. to prepare bromine-chlorine masterbatch.

[0067] (4) 10.91 g of ytterbium (III) acetate tetrahydrate and 1000 g of POE were uniformly mixed and placed in a pelletizer with a maximum melting temperature set at 180° C. to prepare ytterbium masterbatch.

[0068] (5) After 26 g of cesium masterbatch, 49 g of lead masterbatch, 126 g of bromine-chlorine masterbatch, 49 g of ytterbium masterbatch and 150 g of blank POE masterbatch were mixed evenly, 2 g of crosslinking agent TAIC (triallyl isocyanate), 2.4 g of auxiliary crosslinking agent DCP (diisopropyl peroxide), 0.8 g of coupling agent vinyl trimethoxysilane, 2 g of light stabilizer 770 (bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate), 0.8 g of antioxidant 1010 and 0.8 g of anti-PID auxiliary agent (ethoxylated pentaerythritol triacrylate) were added to the feed port, the extrusion temperature was set to 240 ° C and the screw speed was set to 30 rpm for extrusion calendering to obtain a quantum tailored film with a thickness of 0.6 mm.

[0069] (6) Take a battery cell 3 (a crystalline silicon battery cell in this embodiment), place the quantum tailoring packaging film prepared in (5) on its upper surface as the upper packaging film 2, place the quantum tailoring packaging film prepared in (5) on its lower surface as the lower packaging film 4, then place the upper packaging glass 1 on the upper packaging film 2, and then place the lower packaging glass 5 under the lower packaging film 4.

[0070] (7) Put the assembled parts into a laminator for lamination processing to obtain Figure 1 The solar cell containing the quantum tailoring coating shown in the figure has a lamination pressure of 50 kPa, a lamination temperature of 140° C., and a lamination time of 20 min during the lamination process.

[0071] Example 2

[0072] The difference between this embodiment and Embodiment 1 is that POE is replaced by EVA.

[0073] Example 3

[0074] The only difference between this embodiment and Embodiment 1 is that POE is replaced by PVB.

[0075] Example 4

[0076] The only difference between this embodiment and embodiment 1 is that 26 g of cesium masterbatch, 49 g of lead masterbatch, 126 g of bromine and chlorine masterbatch, 73.5 g of ytterbium masterbatch and 125.5 g of blank POE masterbatch are mixed evenly.

[0077] Comparative Example 1

[0078] This comparative example provides a method for preparing a solar cell: take a battery unit 3 (a crystalline silicon battery cell in this comparative example), place an upper packaging film 2 on its upper surface, place a lower packaging film 4 on its lower surface, then place an upper packaging glass 1 on the upper packaging film 2, and then place a lower packaging glass 5 under the lower packaging film 4. Put the assembled components into a laminator for lamination processing to obtain Figure 1 The solar cell shown in the figure has a lamination pressure of 50 kPa, a lamination temperature of 140° C., a lamination time of 20 min, and a packaged component with a bluish-black appearance.

[0079] In this comparative example, the upper packaging film 2 and the lower packaging film 4 are POE films with a thickness of 0.6 mm made from blank POE masterbatch.

[0080] Comparative Example 2:

[0081] This comparative example provides a method for preparing a solar cell: take a battery unit 3 (a crystalline silicon battery cell in this comparative example), place an upper packaging film 2 on its upper surface, place a lower packaging film 4 on its lower surface, then place an upper packaging glass 1 on the upper packaging film 2, and then place a lower packaging glass 5 under the lower packaging film 4. Put the assembled components into a laminator for lamination processing to obtain Figure 1 The solar cell shown in the figure has a lamination pressure of 50 kPa, a lamination temperature of 140° C., a lamination time of 20 min, and a packaged component with a bluish-black appearance.

[0082] In this comparative example, the upper packaging film 2 and the lower packaging film 4 are EVA films with a thickness of 0.6 mm made from blank EVA masterbatch.

[0083] Comparative Example 3

[0084] This comparative example provides a method for preparing a solar cell:

[0085] (1) Prepare 0.4g CsPbCl 1.5 Br 1.5 :Yb (200%) perovskite quantum tailoring quantum dots were uniformly mixed with 400g POE, put into a granulator and set the maximum melting temperature to 180°C to prepare a masterbatch containing quantum tailoring raw materials. CsPbCl 1.5 Br 1.5 :Yb(200%) refers to the Yb doping amount of CsPbCl 1.5 Br 1.5 Twice the amount of substance.

[0086] (2) Add 2g of crosslinking agent TAIC (triallyl isocyanate), 2.4g of auxiliary crosslinking agent DCP (diisopropyl peroxide), 0.8g of coupling agent vinyl trimethoxysilane, 2g of light stabilizer 770 (bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate), 0.8g of antioxidant 1010, and 0.8g of anti-PID auxiliary agent (ethoxylated pentaerythritol triacrylate) to the feed port according to the quantum tailoring masterbatch, set the extrusion temperature to 180°C and the screw speed to 30rpm for extrusion and calendering to obtain a quantum tailoring film.

[0087] (3) Take a crystalline silicon cell and place the quantum tailored encapsulation film prepared in (2) on its upper and lower surfaces respectively, and then place an upper encapsulation glass on the upper surface and a lower encapsulation glass on the lower surface.

[0088] (4) The assembled components are placed in a laminator for lamination to obtain a crystalline silicon cell module containing a quantum tailoring coating, wherein the lamination pressure during the lamination process is 50 kPa, the lamination temperature is 140° C., and the lamination time is 20 min. The packaged module has a blue-black appearance.

[0089] Comparative Example 4

[0090] Take the prepared 1g CsPbCl 1.5 Br 1.5 :Yb (200%) perovskite quantum tailoring raw material was evenly mixed with 1000g UV curing ink, and printed on the inner surface of the upper and lower packaging glass with a 200 mesh, 40μm wire diameter polyester screen and an 80-degree scraper to obtain a quantum tailoring coating. The upper and lower packaging glass were placed in a UV irradiator with the printed surface facing up and the energy was 1000mJ / cm 2 After irradiation with ultraviolet light of 365 nm wavelength for 30 seconds for curing, the steps of packaging, lamination, and testing are exactly the same as those in Example 1.

[0091] In this comparative example, the upper packaging film 2 and the lower packaging film 4 are POE films with a thickness of 0.6 mm made from blank POE masterbatch.

[0092] Test example

[0093] The energy conversion efficiency of the solar cells prepared in Examples 1-4 and Comparative Examples 1-4 was 1.5G (100 mW / cm 2 The test was carried out under the standard test conditions of ), and the test results are shown in Table 1.

[0094] Component peeling force test process: Cut the adhesive films prepared in Examples 1-4 and Comparative Examples 1-4 into 75 mm × 150 mm sizes, and laminate glass / adhesive film / glass in sequence to obtain a laminate, and use a vacuum laminator to press the laminate at a lamination pressure of 50 kPa, a lamination temperature of 140° C., and a lamination time of 20 min to ensure that the adhesive film is fully cross-linked and the adhesive film and the glass are effectively bonded. Then use a tensile tester to test the adhesion between the adhesive film and the glass according to ASTM D903 standard.

[0095] The glass of Examples 1-4 and Comparative Examples 1-3 uses solar ultra-white cloth-textured glass (4 mm thick, 75 mm×150 mm in size), and the glass of Comparative Example 4 uses encapsulated glass that is coated with a quantum tailoring coating and cured according to the method of Comparative Example 4.

[0096] Table 1 Solar cell performance

[0097]

[0098]

[0099] From the comparison between Example 1 and Comparative Example 1, and between Example 2 and Comparative Example 2 in Table 1, it can be seen that the solar cell prepared by adopting the scheme of the present invention can greatly improve its light conversion efficiency and will not cause adverse effects on the component peeling force of the solar cell.

[0100] Comparative Example 3 synthesizes quantum dots first and then adds them, which is a non-in-situ synthesis of quantum dots. The heat resistance of the quantum tailoring material is greatly reduced, and the gain effect is weak after injection molding and lamination. Compared with Comparative Example 3, Example 1 can greatly improve its light conversion efficiency.

[0101] In Comparative Example 4, since the quantum tailoring coating did not undergo a high-temperature injection molding process, the light conversion efficiency was increased to 19.5%, but the adhesion was greatly reduced, and its peel strength was 88.0 N / cm. Compared with Comparative Example 4, Example 1 can ensure the component peeling force of the solar cell and improve the light conversion efficiency.

[0102] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for preparing a quantum tailoring film, characterized in that: The following steps are involved: Step 1, mixing the raw materials required for synthesizing quantum tailored quantum dots with plastic materials to obtain masterbatches containing the corresponding raw materials; Step 2: Mix the masterbatches of quantum tailored quantum dots to form a quantum tailored film.

2. The method for preparing a quantum tailoring adhesive film according to claim 1, characterized in that: The quantum tailoring quantum dots are rare earth doped perovskite quantum dots, and the perovskite quantum dots are composed of: ABX3; Among them, X includes Cl - Br - ,I - At least one of; A includes Cs + 、CH3NH3 + 、CH(NH2)2 + At least one of; B includes Pb 2+ Sn 2+ , Mn 2+ At least one of; The rare earth includes at least one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, yttrium or scandium.

3. The method for preparing a quantum tailoring adhesive film according to claim 2, characterized in that: The step 1 comprises: The raw material containing A is mixed with the plastic material and granulated to obtain a master batch A; preferably, the mass content of the raw material containing A in the master batch A is 0.5-2%; The raw material containing B is mixed with the plastic material and granulated to obtain a master batch B; preferably, the mass content of the raw material containing B in the master batch B is 0.5-2%; The raw material containing X is mixed with the plastic material and granulated to obtain a masterbatch X; preferably, the mass content of the raw material containing X in the masterbatch X is 1 to 3%; The raw material containing rare earth elements is mixed with the plastic material and granulated to obtain the master batch Re; preferably, the mass content of the raw material containing rare earth elements in the master batch Re is 0.5-2%.

4. The method for preparing a quantum tailoring adhesive film according to claim 3, characterized in that: At least one of the following conditions is met: (1) The raw material A includes at least one of cesium stearate, cesium carbonate and cesium acetate; (2) the B-containing raw material includes at least one of lead stearate, lead acetate and lead carbonate; (3) the X-containing raw material includes at least one of octylamine bromide, oleylamine bromide, dimethyldioctadecyl bromide, octylamine chloride, oleylamine chloride, and dimethyldioctadecyl chloride; (4) The raw material containing rare earth elements includes at least one of ytterbium acetate, ytterbium acetate, ytterbium chloride, and ytterbium oxide.

5. The method for preparing a quantum tailoring adhesive film according to claim 3 or 4, characterized in that: Step 2 also includes the step of adding blank masterbatch, wherein the blank masterbatch is prepared by granulating plastic material; Preferably, when the masterbatches are mixed, the mass ratio of masterbatch A: masterbatch B: masterbatch X: masterbatch Re: blank masterbatch is (20.8-31.2): (39.2-58.8): (100.8-151.2): (19.6-98): (180-102).

6. The method for preparing a quantum tailoring adhesive film according to any one of claims 1 to 4, characterized in that: In step 2, after the masterbatches of quantum tailored quantum dots are mixed, the step of adding a crosslinking agent, a co-crosslinking agent, a coupling agent, a light stabilizer, an antioxidant and an anti-PID auxiliary agent is also included.

7. The method for preparing a quantum tailoring adhesive film according to claim 6, characterized in that: At least one of the following conditions is met: (1) The plastic material is ethylene-octene copolymer, polyethylene-polyvinyl acetate copolymer or polyvinyl butyral; (2) The crosslinking agent is selected from one or more of tert-butyl peroxy-2-ethylhexyl carbonate, tert-butyl peroxy-isopropyl carbonate, dibenzoyl peroxide, diisopropyl benzene peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, cyclohexanone peroxide, tert-butyl hydroperoxide, tert-butyl perbenzoate, tert-butyl peracetate, di-(4-tert-butylcyclohexyl) peroxydicarbonate, tert-butyl peroxy-3,5,5-trimethylhexanoate, and triallyl isocyanate; (3) the auxiliary cross-linking agent is selected from one or more of trimethylolpropane triacrylate, 2-trimethylolpropane tetraacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethyl 4-(dimethylamino)benzoate, and diisopropylbenzene peroxide (DCP); (4) The coupling agent is selected from one or more of 3-(methacryloyloxy)propyltrimethoxysilane, 3-glycidylpropyltrimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane, and vinyltrimethoxysilane; (5) The light stabilizer is one or more selected from bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate, poly-{[6-[(1,1,3,3-tetramethylbutyl)-imino]-1,3,5-triazine-2,4-diyl][2-(2,2,6,6-tetramethylpiperidinyl)-amino]-hexylene-[4-(2,2,6,6-tetramethylpiperidinyl)-imino]}; (6) The antioxidant is one or more of a phenolic antioxidant, a phosphite antioxidant and a hindered amine antioxidant; (7) The anti-PID additive is one or more of ethoxylated pentaerythritol triacrylate, aluminum phosphate, titanium phosphate, tin phosphate, zirconium phosphate or bismuth phosphate; (8) The amount of the cross-linking agent added is 0.1 to 1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch; (9) The amount of the co-crosslinking agent added is 0.1 to 1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch; (10) The amount of the coupling agent added is 0.1 to 1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch; (11) The amount of the light stabilizer added is 0.1 to 1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch; (12) The amount of the antioxidant added is 0.1 to 1% of the total mass of each masterbatch of quantum tailored quantum dots + blank masterbatch; (13) The amount of the anti-PID additive added is 0.1 to 1% of the total mass of the masterbatch of quantum tailored quantum dots + the blank masterbatch.

8. A quantum tailoring adhesive film prepared according to the method according to any one of claims 1 to 7.

9. A solar cell, characterized in that: It includes upper packaging glass, upper packaging film, battery unit, lower packaging film and lower packaging glass in sequence; The upper packaging film and / or the lower packaging film is the quantum cutting film according to claim 8; Optionally, the battery unit is any one of a crystalline silicon battery, a perovskite battery, a perovskite-crystalline silicon stacked battery, a dye-sensitized battery, a quantum dot photovoltaic, an organic photovoltaic, a copper indium gallium selenide solar device, and a cadmium telluride thin-film solar device.

10. A method for preparing a solar cell according to claim 9, characterized in that: The method comprises taking a battery unit, placing an upper packaging film and a lower packaging film on the upper and lower surfaces thereof respectively, placing an upper packaging glass on the upper packaging film, placing a lower packaging glass under the lower packaging film, and laminating to obtain the solar cell; Optionally, the lamination pressure during the lamination process is 20 to 90 kPa, the lamination temperature is 80 to 180° C., and the lamination time is 15 to 30 min.